DIGITAL TRANSFORMATION IN THE FIELD OF INFORMATION SECURITY MANAGEMENT - Svetlana Anatolyevna Inozemtseva (Современная наука и инновации)
Digital transformation is the planned transfer of business, social security systems, payment systems etc. in a virtual (digital) space. All this involves the systematic transformation of all business processes, changing the business model that leads to changes in the management of the organization, production processes and human resources. Required for development of mechanisms and methodologies of digital transformation to ensure the parallel development and implementation of protection mechanisms: software, hardware, physical, ethical, legal, etc.